2016
DOI: 10.5664/jcsm.6054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antihypertensive Medications on the Severity of Obstructive Sleep Apnea: A Systematic Review and Meta-Analysis

Abstract: Collectively, findings from these relatively small, short-term studies tend to support the contention that treatment with antihypertensive agents confers a statistically significant, albeit small, reduction in the severity of OSA, which may be more pronounced with the use of diuretics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 54 publications
0
11
1
1
Order By: Relevance
“…Although the improvement of OSAHS is closely correlated to the degree of weight loss, the mechanism for improvement in AHI and LSpO 2 by dapagliflozin in the present study remains unclear. Weight loss maybe one reason, but the change in body composition may have been more important than the reduction in BMI 2022 . Several researches have suggested that diuretic therapy can cause a decrease in AHI in patients with OSAHS, without a marked reduction in body weight 23–26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the improvement of OSAHS is closely correlated to the degree of weight loss, the mechanism for improvement in AHI and LSpO 2 by dapagliflozin in the present study remains unclear. Weight loss maybe one reason, but the change in body composition may have been more important than the reduction in BMI 2022 . Several researches have suggested that diuretic therapy can cause a decrease in AHI in patients with OSAHS, without a marked reduction in body weight 23–26 .…”
Section: Discussionmentioning
confidence: 99%
“…OSA patients with resistant hypertension showed a quite large decrease in blood pressure during CPAP [26]. Antihypertensive drugs, and diuretics in particular, may slightly decrease AHI in OSA [27]. In general, pharmacological treatment to control hypertension is necessary in hypertensive OSA patients, given the small effects of CPAP on blood pressure [28, 29].…”
Section: Common Comorbidities In Osa Patientsmentioning
confidence: 99%
“…The relationship between OSA and hypertension can be bidirectional as intensive blood pressure reductions may influence OSA by stabilizing the upper airways (36). On the other hand, several studies on animals have demonstrated that acute increases in systemic blood pressure cause an inhibitory effect on the EMG of upper airway muscles in cats (37), and anaesthetised dogs (38), thereby facilitating sleep apnea.…”
Section: Bi-directional Relationship Between Osa and Hypertensionmentioning
confidence: 99%